2005
DOI: 10.3892/ijo.27.4.893
|View full text |Cite
|
Sign up to set email alerts
|

Combined treatment of leukemia cells with vitamin K2 and 1α,25-dihydroxy vitamin D3 enhances monocytic differentiation along with becoming resistant to apoptosis by induction of cytoplasmic p21CIP1

Abstract: Vitamin K 2 (VK2) effectively induces apoptosis in leukemia cell lines, including HL-60 and U937. However, combined treatment of cells with VK2 plus la, 25-dihydroxyvitamin D 3 (VD3) resulted in suppression of VK2-inducing apoptosis and pronounced induction of monocytic differentiation as compared with that by VD3 alone. After achieving monocytic differentiation by pre-exposure to VK2 and VD3, the cells became resistant to various apoptotic stimuli including VK2-and H 2 0 2-treatment and serum deprivation. Acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…5). Moreover, we showed that p21 CIP1 and p16 INK4A accumulate primarily in the cytoplasm of p300 inhibited cells, suggesting that the induction of these proteins does not regulate the cell cycle but might have other cellular functions such as previously identified in apoptosis resistance or metastatic inhibition 24,25 . Furthermore, the lack of a requirement of p53, which is usually linked with DDR activation, reinforces our observation that p300 HAT inhibition-induced senescence occurs in the absence of DNA damage.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…5). Moreover, we showed that p21 CIP1 and p16 INK4A accumulate primarily in the cytoplasm of p300 inhibited cells, suggesting that the induction of these proteins does not regulate the cell cycle but might have other cellular functions such as previously identified in apoptosis resistance or metastatic inhibition 24,25 . Furthermore, the lack of a requirement of p53, which is usually linked with DDR activation, reinforces our observation that p300 HAT inhibition-induced senescence occurs in the absence of DNA damage.…”
Section: Resultsmentioning
confidence: 73%
“…We performed nuclear and cytoplasmic cell fractionations and showed that p21 CIP1 and p16 INK4A accumulate primarily in the cytoplasm of curcumin-treated cells (Fig. 5d), suggesting that the induction of these proteins does not regulate the cell cycle but might have other functions 24,25 . Although we cannot exclude that the induction of p21 CIP1 and p16 INK4A might participate in an extra step for stabilizing the cell cycle arrest later in the senescence process, we can conclude that senescence induction by inhibition of p300 HAT activity is independent of the p53/p21 CIP1 and p16 INK4A pathways.…”
Section: Resultsmentioning
confidence: 99%
“…3,4,35,36 Similarly, its ectopically induced expression can either enhance, 19,37,38 or prevent apoptosis induced upon chemotherapy treatment. 39,40 A dual role in apoptosis observed in our study is probably a consequence of p21 protein interaction with particular protein(s) involved in apoptosis triggered by cisplatin and methotrexate. 41 Previous investigations have shown that both the extrinsic and intrinsic apoptotic pathways are triggered by cisplatin in cells lacking p53 expression, which is also in concordance with our results.…”
Section: Discussionmentioning
confidence: 95%
“…The vitamin D3 analog, EB1089, was also reported to induce apoptosis in leukemia cells (16), but other reports reveal that vitamin D3 causes an inhibitory effect on apoptosis of leukemia cells (17,18). These opposing results suggest a necessity of verifying the effects of vitamin D3 on apoptosis before we could suggest any other mechanism responsible for cell death in response to vitamin D3 in HL-60 cells.…”
Section: Inhibition Of Differentiation Does Not Efficiently Diminishmentioning
confidence: 88%
“…In invasive breast cancer cells, down-regulation of Bcl-2 protein is accompanied by an increase in the proapoptotic protein Bax and a release of cytochrome c from the mitochondria followed by poly(ADP-ribose) polymerase cleavage (15). Contrary to the observation that vitamin D3 induces apoptosis in B-cell chronic lymphocytic leukemia cells (16), two studies show that vitamin D3 inhibits apoptosis of myeloid leukemia cells (17,18), suggesting cell type-dependent mechanisms by which vitamin D3 modulates apoptosis.…”
mentioning
confidence: 98%